Geography and the Enlightenment: Patriotic Views of the Port City of Havana, 1761-1791. - Meléndez, Mariselle (Latin American Research Review, 2018)
This article focuses on how two Spanish American Creole writers perceived their port city as a symbol of national prestige, devoted patriotism, and utilitarian significance, at a time when the military and economic status of the port was undergoing transformational changes. It centers on the works of two eighteenth-century Cuban writers, José Martín Félix de Arrate's Llave del Nuevo Mundo, antemural de las Indias Occidentales: La Habana descripta (1761) and Ignacio José de Urrutia y Montoya's Teatro histórico, jurídico y político-militar de la Isla Fernandina de Cuba y principalmente de su capital La Habana (1791), to show the ways in which these authors articulated their love for their country while endowing the port and the port city with local political power and cultural prestige. This sense of "topophilia," a concept described by geographer Yi-Fu Tuan as the "affective bond between people and place," is what guided the aforementioned authors' geographic view of the port.